Ultrasound-enhanced siRNA delivery using magnetic nanoparticle-loaded chitosan-deoxycholic acid nanodroplets - Lee, J; Crake, C; Teo, B; Carugo, D; de Saint Victor, M; Seth, A; Stride, E (Wiley, 2017)
Small interfering RNA (siRNA) has significant therapeutic potential but its clinical translation has been severely inhibited by a lack of effective delivery strategies. Previous work has demonstrated that perfluorocarbon nanodroplets loaded with magnetic nanoparticles can facilitate the intracellular delivery of a conventional chemotherapeutic drug. The aim of this study was to determine whether a similar agent could provide a means of delivering siRNA, enabling efficient transfection without degradation of the molecule. Chitosan-deoxycholic acid nanoparticles containing perfluoropentane and iron oxide (d0 = 7.5 ± 0.35 nm) with a mean hydrodynamic diameter of 257.6 ± 10.9 nm were produced. siRNA (AllStars Hs cell death siRNA) was electrostatically bound to the particle surface and delivery to lung cancer cells and breast cancer cells was investigated with and without ultrasound exposure (500 kHz, 1 MPa peak-to-peak focal pressure, 40 cycles per burst, 1 kHz PRF, 10 seconds duration). The results showed that siRNA functionality was not impaired by the treatment protocol and that the nanodroplets were able to successfully promote siRNA uptake, leading to significant apoptosis (52.4%) 72 hours after ultrasound treatment.